Oscar Wilde’s aesthetic cynicism and humanistic liberalism in the picture of Dorian Gray: A post-modern assessment - Md Mozaffor Hossain (Universitas Merdeka Malang, 2022)
In The Picture of Dorian Gray, Oscar Wilde, regarding myriad aspects of life, comes up with commendable aesthetic notions just before he serves on the table, as to them, direly cynical views. Each of the appealing concepts gives one an intellectually euphoric realization as much as each of the cynic additions, instantly, renders one confused. Surprisingly, the seemingly deliberate twists added to the aesthetic considerations make them more beautiful and thought-provoking. Wilde’s cynical parts characteristically offer an obvious liberalism which profoundly hinges upon humanity. This article intends to investigate into the narrative with the post-modern literary outlooks with the belief that such an appraisal might provide a scholastically apt understanding of Oscar Wilde.DOI: 10.26905/enjourme.v7i2.8346